Redistributed manufacturing of spare parts: an agent-based modelling approach - Haddad, Yousef; Salonitis, Konstantinos; Emmanouilidis, Christos (Elsevier, 2019)
Maintenance and repair activities from the perspective of OEMs are both considerable sources of revenue and expenses, particularly when part of a Product Service System (PSS). It is therefore necessary for an OEM that provides services bundled with products to ensure timely response without significant impact on cost. This paper proposes a make-to-order spare parts supply chain strategy through the adoption of Redistributed Manufacturing (RdM) where the supply chain is shortened and total cost is decreased. An agent-based model that portrays an OEM’s response to repair a failed equipment is developed to exhibit the potential time and cost savings gained by OEMs.
Keywords: redistributed manufacturing; product service system; agent-based modelling